Catatonia in 26 patients with bipolar disorder: clinical features and response to electroconvulsive therapy. (8th December 2015) - Medda, Pierpaolo; Toni, Cristina; Luchini, Federica; Giorgi Mariani, Michela; Mauri, Mauro; Perugi, Giulio
Abstract : Objectives: We describe the clinical characteristics and short‐term outcomes of a sample of inpatients with bipolar disorder with severe catatonic features resistant to pharmacological treatment. Methods: The study involved 26 catatonic patients, resistant to a trial of benzodiazepines, and then treated with electroconvulsive therapy (ECT). All patients were evaluated prior to and one week following the ECT course using the Bush–Francis Catatonia Rating Scale (BFCRS) and the Clinical Global Impression (CGI). Results: In our sample, women were over‐represented (n = 23, 88.5%), the mean (± standard deviation) age was 49.5 ± 12.5 years, the mean age at onset was 28.1 ± 12.8 years, and the mean number of previous mood episodes was 5.3 ± 2.9. The mean duration of catatonic symptoms was 16.7 ± 11.8 (range: 3–50) weeks, and personal history of previous catatonic episodes was present in 10 patients (38.5%). Seventeen (65.4%) patients showed abnormalities at cerebral computerized tomography and/or magnetic resonance imaging and neurological comorbidities were observed in 15.4% of the sample. Stupor, rigidity, staring, negativism, withdrawal, and mutism were observed in more than 90% of patients. At the end of the ECT course, 21 patients (80.8%) were classified as responders. The BFCRS showed the largest percentage of improvement, with an 82% reduction of the initial score. The number of previous mood episodes was significantly lower and the use of anticholinergic and dopamine‐agonist medications was significantly more frequent in non‐responders than in responders. Conclusions: Our patients with bipolar disorder had predominantly retarded catatonia, frequent previous catatonic episodes, indicating a recurrent course, and high rates of concomitant brain structure alterations. However, ECT was a very effective treatment for catatonia in this patient group that was resistant to benzodiazepines.